Who eats What: Unravelling a complex taphonomic scenario in the lacustrine deposits of the late Pleistocene archaeological site, Taguatagua 1, central Chile. (15th January 2023) - Lizama-Catalán, Álvaro; Labarca, Rafael
Abstract: Taguatagua 1 is a late Pleistocene open-air archaeological site located on an ancient lakeshore in central Chile and dated to around 12, 600 cal BP. It presents clear evidence of human and megafauna (Equidae, Gomphotheriidae and Cervidae) interaction that includes burned, fractured and cut-marked bones, as well as tusk and bone-made instruments. Mixed with artefacts and megafauna bones, an outstanding small vertebrate record (Class Actinopterygii, Amphibia, Reptilia, Aves and Mammalia) has also been reported, which has remained largely unstudied. In this paper, we present the first comprehensive taphonomic study of a selected sample of this ensemble. Birds are the most common taxa, followed by anurans, fish and rodents. Surface modifications, bone breakage, skeletal frequencies and the sample's ecological/biological attributes indicate different taphonomic trajectories for an averaged sample. A portion of the ensemble entered the context via predators and natural deaths, but the presence of anthropogenic marks, especially in aquatic birds, and to a lesser extent in Myocastor coypus and Calyptocephalella sp., indicates cultural exploitation of these taxa. These results portray a more precise image of the late Pleistocene hunter-gatherer subsistence strategies in central Chile, which is consistent with the settlement's lacustrine context. Highlights: Taguatagua 1 shows evidence of human consumption of small game, especially waterfowl. Fish and anurans entered to the archaeological deposit mainly via natural deaths. Small caviomorphs were mainly predated, but the large ones were culturally exploited. Taxonomic richness indices suggest a high specialisation in small fauna exploitation.